Effect of fit-for-purpose biochars on rumen fermentation, microbial communities, and methane production in cattle - Martinez-Fernandez, Gonzalo; Kinley, Robert D.; Smith, Wendy J. M.; Simington, Jessica; Joseph, Stephen; Tahery, Sara; Durmic, Zoey; Vercoe, Phil (Frontiers in Microbiology, 2024)
Biochar has gained attention as a possible antimethanogenic supplement for ruminants. However, the effects of biochars on rumen methanogenesis are variable and often contradictory. These effects presumably depend on the types of biochar, parent material source and the administration regimes, in terms of both the form it is offered, and the dosages required to be effective. The objective of this study was to examine the effect of two fit-for-purpose biochars on rumen fermentation, CH4 emissions, and the rumen microbiome of cattle fed roughage diets. Two experiments were conducted - Experiment 1 was a controlled pen trial lasting 56 days and involving 12 steers fed Rhodes grass hay ad-lib. Animals received one of the following treatments mixed with molasses (200 mL per animal/day): Biochar 1 or 2 at four doses – control (0 g biochar/animal/day); low dose: 50 g biochar/animal/day; mid dose 100 g biochar/animal/day and high dose: 200 g biochar/animal/day. Methane emissions were measured using open-circuit respiration chambers . and rumen fluid was collected for rumen microbial and fermentation metabolites analyses. Experiment 2: 45 heifers were selected and grazed together during 60 days in a single paddock to study the effect of biochar on productivity and CH4 emissions. Animals (15 per treatment) were allocated to one of the treatments using an auto-drafter: control (No Biochar, only molasses), Biochar 1 or Biochar 2. Treatments were offered daily to each group at a single dose estimated to be 100 g of biochar/animal/day mixed with molasses. Methane production from individual animals was measured using GreenFeed systems in the field. The biochars decreased CH4 emissions by 8.8-12.9 % in cattle under controlled feeding conditions (experiment 1) with no detrimental effect on rumen fermentation or DMI, and minor changes on rumen bacterial structure associated mainly to Christensenellaceae and Prevotellaceae families. However, under grazing conditions (experiment 2), no significant difference in enteric CH4 emissions or productivity could be detected when the same biochars were supplemented. Further research is required to identify fit-for-purpose biochar types, doses, and delivery methods suitable to achieve a sustained CH4 mitigation for grazing systems without affecting productivity.